(untitled) (Journal of the College of Basic Education, 2024)
The research deals with the political and administrative conditions of Italy during the control of the Ostrogoths, under which they achieved prosperity and security, which made the Byzantine Empire yearn to recover it from them as it was a vital part of the empire. The circumstances of the weakness of the Gothic throne helped achieve the Byzantine goal of taking over Italy, so a military conflict took place between On both sides, the victim was the Italian people, as they suffered from the scourges of war, including poverty, hunger, and murder. The Byzantine Empire’s control over Italy only made the situation worse. Despite Emperor Justinian I’s attempt to organize regulations for Italy, he only achieved tragic results that led to an increase in the suffering of the Italian population.